Squeeze Flow of a Newtonian Fluid under Different Test Speeds - Pham, H. S.; Vu, X. H.; Phan, V. T. (Engineering, Technology & Applied Science Research, 2020)
In this paper, the squeeze flow behavior of Newtonian fluid was investigated with a series of squeeze tack laboratory experiments. The Newtonian fluid was squeezed out radially between two parallel and circular plates. From the flow curves obtained in the squeeze tack experiments, rheological parameters such as yield stress in tension and in squeeze, have been investigated. The results indicate that the values of yield stress in squeeze and in tack of the testing material are relatively small. These values gradually decrease with increasing sample thickness. This shows that the squeezing and tacking process does not affect the testing material, glucose in this case. Although the experimental results are not much, a linear relationship can be found between tensile and squeeze stress of Newton fluid in the experiment. This is especially evident at low test speeds